2020
DOI: 10.15761/ohc.1000198
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanics of implant-supported cantilevered fixed partial dentures: Systematic review of the literature

Abstract: Introduction: Current implant rehabilitations must take into account prosthetic imperatives. Pre-implant planning permits to highlight some unfavorable clinical situations that compete against the ideal implant location. An alternative prosthetic design intending the use of an implant-supported cantilevered bridge may be suggested. Purpose:The main aim of our review is to analyze the biomechanics of fixed partial implant cantilevered restorations as well as the criteria for a reliable choice of this design. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…(23)(24)(25)(26) However, a systematic review on the biomechanics of implant-supported cantilevered xed dental prosthesis suggested the use of cantilever designs especially mesial cantilevers as a prosthetic alternative avoiding more invasive surgical procedures, yet the clinical criteria as cantilever length, occlusion scheme, implant number and diameter should be highly considered. (27) Regarding implant prosthetic materials, The second null hypothesis was rejected as our results showed speci c inter-relationships between the resultant stresses in the different structures and the elastic modulus of the prosthetic material. Rigid zirconia induced the highest von Mises stresses in the prosthesis (105.0 MPa) and the lowest values in implant (48.9 MPa) and bone (19.6 MPa) regardless the prosthetic design, while resilient PEKK generated the lowest stresses in the prosthesis (35.4 MPa) and the highest von Mises stresses in the implant (111.6 MPa) and bone (100.0 MPa).…”
Section: Discussionmentioning
confidence: 86%
“…(23)(24)(25)(26) However, a systematic review on the biomechanics of implant-supported cantilevered xed dental prosthesis suggested the use of cantilever designs especially mesial cantilevers as a prosthetic alternative avoiding more invasive surgical procedures, yet the clinical criteria as cantilever length, occlusion scheme, implant number and diameter should be highly considered. (27) Regarding implant prosthetic materials, The second null hypothesis was rejected as our results showed speci c inter-relationships between the resultant stresses in the different structures and the elastic modulus of the prosthetic material. Rigid zirconia induced the highest von Mises stresses in the prosthesis (105.0 MPa) and the lowest values in implant (48.9 MPa) and bone (19.6 MPa) regardless the prosthetic design, while resilient PEKK generated the lowest stresses in the prosthesis (35.4 MPa) and the highest von Mises stresses in the implant (111.6 MPa) and bone (100.0 MPa).…”
Section: Discussionmentioning
confidence: 86%
“…Thus, to reach a successful design the clinical criteria that affect stress dissipation should be well-known. Such knowledge can decrease mechanical failures and improve the longevity of the fixed free designed prostheses (Amine et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Such knowledge can decrease mechanical failures and improve the longevity of the xed free designed prostheses. [19] Conclusions Pure PEKK is not recommended as a xed prosthesis material with the free pontic design.…”
Section: However Other Researches Had An Opposing Opinion and Differe...mentioning
confidence: 99%